Increasing Productivity and Recovering Nutritional, Organoleptic, and Nutraceutical Qualities of Major Vegetable Crops for Better Dietetics - Raju Lal Bhardwaj; Latika Vyas; Mahendra Prakash Verma; Suresh Chand Meena; Anirudha Chattopadhyay; Neeraj Kumar Meena; Dan Singh Jakhar; Sita Ram Kumawat (Foods)
The intensive use of chemical fertilizers for vegetable cultivation to achieve higher productivity causes soil degradation, resulting in an alarming decline (25–50%) in nutritional quality and a reduction in a wide variety of nutritionally essential minerals and nutraceutical compounds in high-yielding vegetable crops over the last few decades. To restore the physio-chemical and biological qualities of soil as well as the nutritional and nutraceutical qualities of fresh produce, there is a growing desire to investigate the remedial impacts of organic sources of nutrition. This study specifically focused on the impact of six different ratios of chemical fertilizers and organic sources with microbial inoculation on vegetable productivity, nutrition quality, and soil health parameters. Results show that replacing chemical fertilizers with organic sources in the presence of a microbial consortium supports the proliferation of the microbial population in the soil rhizosphere and improves the nutritional status and physico-chemical quality of soil, which is the area around the roots of plants where maximum nutrient uptake occurs. This combination of factors significantly recovers overall soil quality, increasing crop productivity by 13.58 to 18.32 percent in tomato, brinjal, and okra. Experimental findings likewise indicate that an assortment of organic sources with a microbial consortium significantly recovers the abundance of beneficial microbes and earthworms in the rhizosphere, which leads to an improvement in nutritional, organoleptic, and nutraceutical quality, with higher antioxidant contents in all three vegetables grown in arid climate conditions.